2007
DOI: 10.2165/00063030-200721030-00002
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Mapping

Abstract: Antibodies are an effective line of defense in preventing infectious diseases. Highly potent neutralizing antibodies can intercept a virus before it attaches to its target cell and, thus, inactivate it. This ability is based on the antibodies' specific recognition of epitopes, the sites of the antigen to which antibodies bind. Thus, understanding the antibody/epitope interaction provides a basis for the rational design of preventive vaccines. It is assumed that immunization with the precise epitope, correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(122 citation statements)
references
References 86 publications
0
114
0
Order By: Relevance
“…B cell epitopes are typically categorized as being either sequential (linear, continuous) or conformational (discontinuous) [35,58,59,60,61]. Recently, there has been considerable debate over the clinical importance and relevance of the two epitope forms, and several studies have shown conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…B cell epitopes are typically categorized as being either sequential (linear, continuous) or conformational (discontinuous) [35,58,59,60,61]. Recently, there has been considerable debate over the clinical importance and relevance of the two epitope forms, and several studies have shown conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Simpler epitopebased vaccines, accentuating neutralizing epitopes, may prove to be an efficient alternative for vaccine design. A better understanding of the dynamics of HIV-1 envelope interactions with its receptors, and in particular those of monomeric gp120, might contribute to the ultimate task of generating such an epitope-based vaccine for AIDS (87). …”
Section: Fig 11mentioning
confidence: 99%
“…Methods for epitope mapping include X-ray crystallography, NMR spectroscopy, and a variety of antigen manipulation/antibody binding analysis techniques [ Gershoni et al, 2007 ]. The method described here provides a means to use NGS datasets with currently available prediction software to identify candidate epitope sites, reducing the number of target regions for fine mapping via costly and time-consuming mutagenesis methods such as alanine substitution [ Kronqvist et al, 2010 ].…”
Section: Resultsmentioning
confidence: 99%
“…Use of NGS with prediction methods can help reduce development time for diagnostics, therapeutics and vaccines that require detailed knowledge of antigenic epitopes [Gershoni et al , 2007; Rojas et al , 2014]. For the described protocol, the most time-consuming activity is library generation.…”
Section: Resultsmentioning
confidence: 99%